ORAL 5-HYDROXYTRYPTOPHAN (5-HTP) DOES NOT AFFECT GROOVED PEGBOARD TEST PERFORMANCE - GENDLE, MATHEW H. (Journal of the North Carolina Academy of Science, 2017)
There is limited knowledge of the neurocognitive effects of the serotonin precursor 5-hydroxytryptophan (5-HTP), which is sold over-the-counter as a nutritional supplement. Animal studies have demonstrated that exogenous 5-HTP promotes the production of ectopic serotonin in dopaminergic neurons—an effect that may reduce dopamine output in these cells. Behavioral studies in humans have demonstrated specific 5-HTP induced cognitive deficits on the IowaGambling Task and the Tower of London task that are likely the result of reduced forebrain dopamine. However, it remains unclear if 5-HTP induced performance decrements observed on the Tower of London task were the result of a motor or cognitive impairment. The objective of this double-blind, placebo-controlled study was to clarify this point by determining if oral administration of 150 mg of 5-HTP disrupts fine motor control, as measured by the Grooved Pegboard Test. Seventy five university undergraduates received either a placebo or 5-HTP and completed the Grooved Pegboard Test. The groups did not differ in the amount of time needed to complete the place (p = 0.67) and remove (p = 0.48) components of the Grooved Pegboard Test. Therefore, 5-HTP induced reductions in performance on the Tower of London task appear to be cognitive in nature, and are unlikely to be the result of fine motor impairment (as measured by the Grooved Pegboard Test). These results also provide important safety information for 5-HTP by demonstrating that a 150 mg oral dose does not generally alter fine motor function.